Building the Resilience of Smallholder Farmers to Climate-Induced Pests and Diseases Through Promotion of CS-IPM Innovations - Adomako, Joseph; Narveh, Ernestina; Yeboah, Stephen; Amankwa-Yeboah, Patricia; Frimpong-Anin, Kofi; Haleegoah, Joyce; Adablah, Richard (2024)
Yam and Sweetpotato are important value chains in Ghana's Bono East and Central regions. Issues of climate variability, pests, and disease continue to affect the productivity of the crops and deny farmers the desired yield and benefit. Promoting validated CSA innovations has the potential to increase resilience and improve the livelihood of vulnerable farmers to the negative effects of climate change. To enhance the adoption of climate-smart innovations, CSA hubs were established across 25 communities in three districts in Bono East (Techiman North, Kintampo North, and Kintampo South) and 2 districts in the central region (Cape Coast and KEEA) where unpredicted environmental conditions are affecting crop production. To promote ownership of the innovation hubs, facilitate access to innovations and promote farmer-to-farmer transfer of knowledge, CSA farmer platforms consisting of mainly of farmers, and other stakeholders like marketers, AEA Officers and opinion leaders in the community to manager the community hubs. The innovations being promoted are aimed at helping farmers improve soil moisture conservation, reduce the abuse and negative consequences of inorganic pesticides, increase soil microflora diversity for improved soil health, improve yield, and subsequently increase the income of farmers.  Specifically, the use of Trichoderma powder and the application of compost as new validated CSA technologies were introduced to yam farmers for use as biofertilizers and biopesticides to improve soil conditions and protect seed and soil-borne pathogens. Also, different sweet potato varieties plus the use of neem leaf powder and onion as a border were introduced as new validated CSA technologies.